Peningkatan Performa Mesin Dapur Semi Kupola Menggunakan Metode Total Productive Maintenance (TPM) Dan 5S (Studi Kasus: CV. Sispra Jaya Logam Pekanbaru) - Randa, Nofri; Susilawati, Anita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Total Productive Maintenance is an innovative approach to maintenance that optimizes equipmenteffectiveness, eliminates damage and develops autonomous maintenance by the operator through daily activitiesinvolving all workers. This study aims to improve the performance of semi-cupola furnace machine byimplementing Total Productive Maintenance and 5S maintenance strategies as work culture in CV. Sispra JayaLogam. The steps of method were collect data, compute the value of Overall Equipment Effectiveness (OEE),Six Big Losses analysis, statistical analysis with SPSS 20 and proposed improvement using 5S method. Theresult of this research was revealed the OEE value rate in June 2017 period that was 84,09%, which was havenot yet fulfill world class OEE standard (85%). From the analysis of six big losses, the most dominant factorinfluences the OEE value, namely set up and adjustment losses, and idling losses with value rate was 22.33%and 22.33% respectively. Based on Pareto chart and fishbone diagrams analyses may be caused by lessresponsive operators and lack of machine maintenance. To improve the performance of semi-cupola furnacemachine, it is necessary to make improvements using the 5S method and implementing the TPM pillar such asplanned maintenance and autonomous maintenance.Keywords : TPM, Method 5S, Overall Equipment Effectiveness (OEE), Six Big Losses, Fishbone Diagram.